Peningkatan Kemampuan Bertanya dan Keaktifan Berkomunikasi Peserta Didik melalui Penerapan Model Inkuiri Terbimbing - Amiasih, Tri; Santosa, Slamet; Dwiastuti, Sri (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
The research aimed to improve student’s questioning ability and communication activness through of  Inquiry model. The research was a Classroom Action Research that performed within 3 cycles used  Inquiry model. The research partisipans were 38students of XI IPA 4 SMA N Karangpandan academic year 2015/2016. The validity of the data used technique of triangulation method. The research used qualitative descriptive analysis techniques. The  research result showed improvement of students’s quantity question from71 questions in cycle I to 72 questions in cycle II, and 108 questions in cycle III. Student’s question quality improved from C1 to C4 in the kognitif level of thingking. Improvement in each indicator of communication activeness showed 44,08% in listening teacher during class, 43,41% in listening peer presentation during class, 61,84% in answering question asked by teacher or friend, 46,05% in asking question during class, and 63,15% in giving opinion during discussion.The conclusion of the research showed improvement of student’s questioning ability and communication activness through Guided Inquiry model.